Deep recession and financial instability or a new long wave of economic growth for US capitalism? A regulation school approach - O'Hara, Phillip (Sage Publications, 2003)
This article investigates whether a new mode of regulation is being developed or has already evolved in the United States to promote long wave upswing during the early years of the new millennium. The regime of accumulation is scrutinized, but neither sustainable productivity nor demand seems to be forthcoming. Institutional forms are then studied- global relations, the state, and finance- and found to be lacking. Periodic deep recession and financial instability are thus likely until suitable changes emerge because long wave upswing has not yet emerged.